2018
DOI: 10.3390/cancers10080265
|View full text |Cite
|
Sign up to set email alerts
|

Organotypic 3D Models of the Ovarian Cancer Tumor Microenvironment

Abstract: Ovarian cancer progression involves multifaceted and variable tumor microenvironments (TMEs), from the in situ carcinoma in the fallopian tube or ovary to dissemination into the peritoneal cavity as single cells or spheroids and attachment to the mesothelial-lined surfaces of the omentum, bowel, and abdominal wall. The TME comprises the tumor vasculature and lymphatics (including endothelial cells and pericytes), in addition to mesothelial cells, fibroblasts, immune cells, adipocytes and extracellular matrix (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…To faithfully reproduce human ovarian cancer in vivo, in 3D organotypic cell culture models, cell–ECM interactions may recreate tumor progression step by step in vitro. [ 196 ] By the different ECM components in vitro, the inherent role of cell–ECM interactions are identified in the transformation of the initiating cancer cells into inert, metastatic, and resistant cancer cells. However, synthetic ECM components available restrain the organotypic models to achieve the primary tissue constructs, including access to tissue heterogeneity and the lifespan of the 3D cultures.…”
Section: Instructive Cell Constructs In Tissue Engineering and Precismentioning
confidence: 99%
See 1 more Smart Citation
“…To faithfully reproduce human ovarian cancer in vivo, in 3D organotypic cell culture models, cell–ECM interactions may recreate tumor progression step by step in vitro. [ 196 ] By the different ECM components in vitro, the inherent role of cell–ECM interactions are identified in the transformation of the initiating cancer cells into inert, metastatic, and resistant cancer cells. However, synthetic ECM components available restrain the organotypic models to achieve the primary tissue constructs, including access to tissue heterogeneity and the lifespan of the 3D cultures.…”
Section: Instructive Cell Constructs In Tissue Engineering and Precismentioning
confidence: 99%
“…C) A546 lung cancer cells; when seeded on different EFK8 hydrogels, tumor spheroidal colony growth pattern is formed in 1.25 mg mL −1 EFK8 peptide hydrogel, 5.0 mg mL −1 EFK8 peptide hydrogel, and 1.25 mg mL −1 EFK8‐SWNT hybrid hydrogel (adapted with permission. [ 196 ] Copyright 2018, Elsevier Ltd).…”
Section: Instructive Cell Constructs In Tissue Engineering and Precismentioning
confidence: 99%
“…Results indicated that the created 3D in vitro cervical cancer model showed stratified epithelial layers and expressed the same types and patterns of differentiation marker proteins as seen in corresponding in vivo tissue in either normal cervical or cervical cancerous tissues. Additionally, other 3D microfluidic systems have been investigated to mimic ovarian cancer environments [58,83,85]. For example, a microfluidic platform of the peritoneum was constructed to mimic ovarian cancer spheroids in the peritoneal cavity with mesothelial cells under hydrodynamic conditions.…”
Section: Bioengineering and Female Reproductive Cancersmentioning
confidence: 99%
“…Factors within the extracellular matrix (ECM) have also been reported to offer the complex milieu that facilitates the necessary interaction between ovarian follicles and their surroundings to ensure follicles growth and development. Members of the thrombospondin (TSP) family also belong to this group of ECM proteins [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%